Governance And Policy Frameworks For Promoting Religious Tolerance In Pluralistic Nations - Mochammad Syafiuddin Shobirin; Mohammad Zakki (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
: Religious tolerance is a vital pillar for maintaining social cohesion and peaceful coexistence in pluralistic nations. This study examines governance structures and policy frameworks that foster interfaith harmony within multicultural contexts. Using a library research approach, this paper analyzes scholarly articles, government documents, international reports, and legal frameworks related to religious freedom and tolerance. The findings reveal that effective promotion of religious tolerance relies on three interrelated aspects: (1) the formulation of inclusive policies that guarantee freedom of religion and belief, (2) institutional governance mechanisms that strengthen cooperation between state institutions, religious organizations, and civil society, and (3) educational initiatives aimed at shaping tolerant attitudes and preventing radicalization. Comparative analysis of policies from several pluralistic countries shows that success is closely linked to multi-stakeholder collaboration, transparent legal frameworks, and consistent implementation supported by effective monitoring systems. This study concludes that governments must adopt a holistic approach combining legal, institutional, and educational strategies to build resilient societies capable of embracing diversity while minimizing interreligious conflicts. Future research should explore the impact of digital governance and social media policies on shaping inclusive narratives and countering religious extremism.